PEMANFAATAN e-WOM DALAM KEGIATAN KOMUNIKASI PEMASARAN PRODUK ES KRIM AICE - IRAWATI SRI WULANDARI (CoverAge: Journal of Strategic Communication, 2020)
The growth of the ice cream industry in Indonesia is experiencing rapid progress since the last four years. Aice as a new producer in the Indonesian ice cream industry began to circulate in Indonesia since 2015. A number of certificates and awards obtained by Aice show that Aice is able to pursue and even surpass other brands that have long been circulating in the community.The purpose of this study is to describe the e-WOM activities conducted by Aice ice cream. This study uses a qualitative descriptive approach to describe how e-WOM activities carried out by Aice in an effort to gain consumer trust so that Aice is able to get the TOP Brand in 2019. This study found that the marketing communication strategy carried out by Aice ice cream uses e-WOM through Instagram @ aiceindonesia is done to fulfill the five general objectives of social media marketing, namely relationship building, brand building, publicity, promotions, and market research.